Rett Syndrome and Mitochondrial Enzyme Deficiencies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
Three children with Rett syndrome and normal muscle mitochondrial structure but abnormalities in mitochondrial respiratory chain enzymes are reported from the Departments of Neurology and Pediatrics, Loyola University, Stritch School of Medicine, Maywood, IL.